Functional hyperbranched polymers with advanced optical, electrical and magnetic properties. (29th August 2014) - Wu, Wenbo; Tang, Runli; Li, Qianqian; Li, Zhen
Abstract : This review summarizes the recent progress in functional HBPs and their application in optics, electronics and magnetics, including light-emitting devices, aggregation-induced emission materials, nonlinear optical materials, chemosensors, solar cells, magnetic materials, etc., and provides outlooks for further exploration in the field. Abstract : As one kind of important functional material, those with advanced optical, electrical and magnetic characteristics have attracted increasing attention due to their essential and irreplaceable role in the daily life of humans. In particular, optical, electrical and magnetic hyperbranched polymers (HBPs) exhibit some unique properties, partially derived from their highly branched topological structures. This review summarizes the recent progress in the field of functional HBPs and their application in optics, electronics and magnetics, including light-emitting polymers, nonlinear optical materials, chemosensors, solar cells, magnetic materials, etc., and also gives some outlooks for further exploration in this field at the end of this paper.